Platelet-rich plasma in arthroscopic rotator cuff repair: a meta-analysis of biomaterial efficacy and future directions for personalized sports medicine - Donghua, Fan; Wei, Lu; Di, Sun; Pu, Ying; Qiang, Wang; Yingchao, Shen; Mingfei, Shi; Xin, Sun (Frontiers in Bioengineering and Biotechnology, 2026)
BackgroundRotator cuff tears represent a prevalent musculoskeletal challenge with high postoperative retear rates despite surgical advances. Platelet-rich plasma (PRP) has emerged as a promising biological adjunct in arthroscopic repair, though clinical evidence remains inconsistent regarding its efficacy in improving structural and functional outcomes.MethodsThis PRISMA-guided meta-analysis evaluated 13 randomized controlled trials (n = 880 patients) comparing PRP-augmented versus conventional arthroscopic rotator cuff repair. Primary outcomes included retear rates and functional scores (UCLA, Constant, SST, ASES, VAS). Statistical analysis employed fixed/random-effects models with subgroup analyses of PRP formulations and tear characteristics.ResultsPRP augmentation significantly improved functional outcomes, with mean differences of 1.82 points (95% CI: 1.13–2.51) for UCLA scores, 2.31 points (95% CI: 1.02–3.61) for Constant scores, and 0.43 points (95% CI: 0.11–0.75) for SST scores (all p < 0.01). VAS pain scores decreased by 0.23 points (95% CI: −0.41 to −0.05, p = 0.01). However, retear rates showed no significant reduction (RR = 0.71, 95% CI: 0.48–1.05, p = 0.09). Benefits were most pronounced in medium/large tears treated with leukocyte-poor PRP and double-row repairs (I2 = 0–40% for functional outcomes). Conclusion: While PRP enhances early functional recovery and pain control after rotator cuff repair, its capacity to improve structural integrity remains unproven. Clinical implementation requires standardization of PRP protocols and targeted application in patients with larger tears. Future research should investigate optimized biomaterial formulations and personalized treatment strategies.